2018
DOI: 10.1016/j.tcs.2017.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling series-parallel task graphs to minimize peak memory

Abstract: We consider a variant of the well-known, NP-complete problem of minimum cut linear arrangement for directed acyclic graphs. In this variant, we are given a directed acyclic graph and we are asked to find a topological ordering such that the maximum number of cut edges at any point in this ordering is minimum. In our variant, the vertices and edges have weights, and the aim is to minimize the maximum weight of cut edges in addition to the weight of the last vertex before the cut. There is a known, polynomial ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…graphs that only comprise of series and parallel compositions of other SP-graphs and the base case of a single node. Optimal memory-aware scheduling of SP-graphs has been solved with a polynomial-time algorithm by [17] based on [21]. We implemented this algorithm and adjusted the task model to match that of DNN inference.…”
Section: Memory-aware Schedulingmentioning
confidence: 99%
“…graphs that only comprise of series and parallel compositions of other SP-graphs and the base case of a single node. Optimal memory-aware scheduling of SP-graphs has been solved with a polynomial-time algorithm by [17] based on [21]. We implemented this algorithm and adjusted the task model to match that of DNN inference.…”
Section: Memory-aware Schedulingmentioning
confidence: 99%
“…Those methods always target to shorten the execution time by smartly selecting the execution route of DAG of the parallel tasks. Some scheduling methods not only try to shorten the execution time, but also try to improve performance of other aspects, such as reducing peak memory [27], the energy consumption [28,29,30] and so on. K. Enver et al, "tried to reduce the peak memory in a parallel execution environment.…”
Section: Related Workmentioning
confidence: 99%
“…Sethi [4] showed that this problem is NP-complete for general task graphs. Further study showed that the problem is solvable in polynomial graphs for tree-shaped graphs [5], or recently series-parallel graphs [6].…”
Section: Introductionmentioning
confidence: 99%